Brazilian network for gestational trophoblastic disease study group consensus on management of gestational trophoblastic disease - Braga, Antonio [UNESP]; de Souza, Priscila Oliveira [UNESP]; dos Santos Esteves, Ana Paula Vieira [UNESP]; Padrón, Lilian [UNESP]; Uberti, Elza [UNESP]; Viggiano, Maurícío [UNESP]; Sun, Sue Yazaki [UNESP]; Maestá, Izildinha [UNESP]; Elias, Kevin M. [UNESP]; Horowitz, Neil [UNESP]; Berkowitz, Ross [UNESP]; Grillo, Bruno; et al. (My University, 2018)
OBJECTIVE: To present the Brazilian Network for Gestational Trophoblastic Disease Study Group consensus on management of gestational trophoblastic disease (GTD). STUDY DESIGN: The modified Delphi technique was used in this study to obtain a consensus among Brazilian specialists on the treatment of GTD. For the 64 statements listed, each participant was asked to assign a Likert scale value according to their agreement. The RAND/UCLA method was used to define the level of consensus among the specialists. RESULTS: The response rate of the potential study participants after the 2 rounds was 40/47 (85%). Of the 64 statements presented, there was an agreement on 54/64 (84%). The situations of disagreement were as follows: 1/12 (8%) statements in the section on diagnosis of GTD, 5/10 (50%) statements in the section on treatment of hydatidiform mole (HM), 2/16 (12.5%) statements in the section on diagnosis of gestational trophoblastic neoplasia (GTN), 1/14 (7%) statements in the section on treatment and followup of GTN, and 1/5 (20%) statements in the section on appropriate time to allow pregnancy after HM and GTN. CONCLUSION: This guideline will serve to standardize the conduct among the Brazilian GTD reference centers as well as to guide the new specialized services that may arise and eventually to physicians who may need to treat cases of GTD.
Keywords: Brazil; Gestational trophoblastic disease; Hydatidiform mole; Rare cancers